Response of okra (abelmoschus esculentus (L.) moench) to biofertilizers. - Anisa N A (Department of Olericulture, College of Horticulture, 2011)
An investigation on the effect of biofertilizers on growth and yield of okra was carried out in the Department of Olericulture, College of Horticulture, Vellanikkara during 2010-11. Okra variety Arka Anamika was used for the study. The experiment was laid out in Randomised Block Design with thirteen treatments and three replications. The biofertilizers (Azospirillum, Arbuscular Mycorrhizal Fungi and Frateuria) were applied @ 2 kg/ha. The treatments included sole inoculation of biofertilizers along with FYM (T1, T2, T3), dual inoculation along with FYM (T4, T5, T6), inoculation of all the three biofertilizers along with FYM, applied as single dose (T7) and double dose (T8), inoculation of all the three biofertilizers along with FYM and inorganic (½, ¾, full dose) fertilizers (T9, T10, T11), application of all the three biofertilizers without FYM (T12) and control (T13- KAU POP). The study revealed that the treatment where Azospirillum, AMF and Frateuria were inoculated along with double dose of FYM (T8) and the treatment where all the three biofertilizers were applied along with FYM and ¾ NPK (T10) exhibited superiority in terms of growth parameters. The relative chlorophyll content (48.73 SPAD Units) and total dry matter production (350.50 g/plant) were the highest in plants supplied with double dose of FYM along with biofertilizers. The earliest flowering (39.67 days) and harvesting (46.33 days) were recorded in plants inoculated with AMF and Frateuria along with FYM (T6). The treatment T8 (double dose of FYM along with Azospirillum, AMF and Frateuria) recorded the maximum fruit weight (19.80 g), fruit girth (6.17 cm) and number of seeds per fruit (82.89). It was followed by the treatment T10 (FYM, inorganic fertilizers (¾) and biofertilizers). Plants treated with double dose of FYM, Azospirillum, AMF and Frateuria (T8) recorded the highest number of fruits per plant (31.67), fruit yield per plant (544.40 g) and total fruit yield (16.33 tha-1). It was followed by integrated application of FYM, inorganic fertilizers (¾) and biofertilizers (T10). The crude protein content of okra fruit was higher in treatments where all the three biofertilizers were applied. The treatment T10 where FYM, inorganic fertilizers (¾) and biofertilizers were applied, recorded the highest beta carotene content (94.33 µg/100g). Shelf life (6.67 days) was more in plants treated with all the three biofertilizers and FYM (T7 and T8). Higher nutrient content and uptake was observed in treatments where all the three biofertilizers were applied. Application of biofertilizers resulted in improvement of soil parameters like organic carbon, available N, P2O5 and K2O, pH and electrical conductivity. The population of Azospirillum, AMF and Frateuria in the rhizosphere was also enhanced by the use of biofertilizers. Regarding the economics of cultivation the highest B:C ratio of 2.49 was recorded in T8, where double dose of FYM was applied along with all the three biofertilizers. It was followed by the treatment T10 which recorded a B:C ratio of 2.42. It can be concluded that inoculation of biofertilizers enhanced the growth, yield and quality of okra. The available nutrient status and health of the soil was also improved by biofertilizer application. Overall assessment indicated that combined application of all the three biofertilizers along with double dose of FYM was the best, with respect to growth and yield. The second best performance was obtained when FYM, inorganic fertilizers (¾) and biofertilizers were applied signifying that a reduction of 25 per cent chemical fertilizers is possible by using biofertilizers.